DELIK PERDAGANGAN ORANG TERHADAP ANAK BUAH KAPAL (ABK) BERKEWARGA NEGARAAN INDONESIA - Yashica Nedhypraha Aprillyzegha (Universitas Stikubank, 2023)
Judicial practice in dealing with cases of criminal acts of trafficking in persons in Decision No. 48/Pid. Sus/2021/PN Crb. and Decision No. 49/Pid. Sus/2021/PN Crb. As is known, the panel of judges delivered their decisions in two decisions of the Cirebon District Court, namely Decision Number 48/Pid.Sus/2021/PN. Cirebon and Decision No. 49/Pid.Sus/2021/PN. Cirebon, which show the lack of justice and legal protection for victims of human trafficking in Indonesia. In fact, Indonesia is a sovereign country that is obliged to protect its citizens by the Constitution of the Republic of Indonesia. Victims of the crime of trafficking in persons receive a form of legal protection not only in the form of criminal sanctions against the perpetrators of Law No. 21 of 2007, but must also receive protection, prevention, and eradication of means or forms of institutions for the crime of trafficking in persons.